(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the sorption characteristics of the surface of the Arolboi mobile sand-soils were studied by chemically strengthening the newly synthesized water-soluble polymers with the help of hydrophobic and hydrophilic substances.